Male Urogenital Disorders and Metabolic Syndrome: Possible Links, Characteristics and Potential Treatment Strategies - Oztekin, Cetin V.; Kaya-Sezginer, Ecem; Yilmaz-Oral, Didem; Gur, Serap (Current Pharmaceutical Design, 2018)
Background: Metabolic syndrome (MetS), as a cluster of metabolic derangements which are major risk factors for vascular disease is one of the most important threats to public health. Although the epidemiological and limited amount of basic science and clinical evidence link MetS to several male urogenital disorders, a holistic approach aiming to define common mechanistic pathways and new possible therapeutic targets are lacking. Objective: The current review has focused on providing scientific evidence on the role of MetS and its components on male urogenital disorders and the definition of new therapeutic targets. Method: In this review, current clinical and basic science literature were assessed examining the role of MetS in etiology and pathogenesis of male urogenital disorders and performed through PubMed from 2000 to May 2017. Results and Conclusion: MetS shows an important association with common male urogenital disorders such as benign prostatic enlargement, lower urinary tract symptoms, erectile dysfunction, infertility and renal disease. MetS affects male urogenital system mainly through endocrine and vascular mechanisms. Obesity, hypogonadism, obesity-induced androgen deficiency, hyperinsulinemia and inflammation are the mechanisms commonly involved and may act as potential targets for MetS-male urogenital system interrelations. Future studies are needed to evaluate the therapeutic approaches for intervention in MetS-male urogenital disease relations.
Keywords: lower urinary tract symptoms